The Caribbean (the English-speaking islands) in pictures. - Evans, Lancelot O.; Davis, Philip T.; Lewis, David G., 1922- (New York, Sterling Pub. Co., 1971)
Reviews the government, geography, and way of the life of the Bahamas, Virgin Islands, Barbados, Trinidad, and Tobago.
Keywords: West Indies -- Pictorial works; Caribbean, English-speaking -- Pictorial works; West Indies